Dasar Program Perencanaan dan Perancangan Arsitektur (DP3A)Pengembangan Rumah Sakit PKU Muhammadiyah Kabupaten Demak(Penguatan Kesan Islami) - Abidin, Agus; , Ir. Indrawati, MT (2017)
Hospital of PKU Muhammadiah Demak is a hospital built on the shared commitment of the citizens of Muhammadiyah Demak to improve well-being and health. The hospital was originally planned with a C grade, but to answer the needs of Demak Regency health hospital was developed into class B hospital. Hospital stands above the Waqf land from H Drs Sunaryo, therefore this hospital will be named PKU Hj. FatimahSulchan. The name is taken from where the elderly wakif. Improvement of facilities and service at the hospital was emphasized on public services (clinic) and the increased capacity of the hospitalization. The development of the hospital is oriented on the concept of Islamic Nuances. This concept is carried with the purpose of Dawah of Islam amar ma'ruf nahi it in order to enforce unity in order to develop the mental, moral, and cultural. This concept also invite all the people to maintain the relationship between people, the environment, and the creator. Keywords: hospitals, Facilities and service, the concept of Islamic